Burned area mapping across the Arctic-boreal zone with Landsat and Sentinel-2 imagery - Stefano Potter; Yili Yang; Arden Burrell; Anna Talucci; Andrew A. Clelland; Sander Veraverbeke; James T. Randerson; Scott J. Goetz; Logan T. Berner; Michelle C. Mack; Xanthe J. Walker; Susan M. Natali; et al. (International Journal of Remote Sensing, 2026)

Connecting Landscapes: A decision support system to facilitate conservation led development - Patrick Jantz; David W. Macdonald; Ivan Gonzalez; Andrew J. Hearn; Żaneta Kaszta; Erin L. Landguth; Dawn Burnham; Scott J. Goetz; Katherine A. Zeller; Andrew J. Loveridge; Samuel Cushman (Environmental Modelling & Software, 2025)

Changes in GEDI-based measures of forest structure after large California wildfires relative to pre-fire conditions - Matthew L. Clark; Christopher R. Hakkenberg; Tim Bailey; Patrick Burns; Scott J. Goetz (Remote Sensing of Environment, 2025)

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

High thermal quality rookeries facilitate high thermoregulatory accuracy in pregnant female rattlesnakes - Haley A. Moniz; Jack H. Buck; Hayley L. Crowell; Scott M. Goetz; Trevor D. Ruiz; Emily N. Taylor; Scott M. Boback (Journal of Thermal Biology, 2024)

Opinion of the Scientific Committee on health, environmental and emerging risks on the safety of titanium dioxide in toys - Theo G. Vermeire; Peter Hoet; Rodica-Mariana Ion; Renate Krätke; Ana Proykova; Marian Scott; Wim H. de Jong; Laurent Bodin; Maria Dusinska; Maciej Stepnik; Susan W.P. Wijnhoven; Herman Autrup; et al. (Regulatory Toxicology and Pharmacology, 2024)

Decadal impacts of wildfire fuel reduction treatments on ecosystem characteristics and fire behavior in alaskan boreal forests - Melissa A. Boyd; Xanthe J. Walker; Jennifer Barnes; Gerardo Celis; Scott J. Goetz; Jill F. Johnstone; Nicholas T. Link; April M. Melvin; Lisa Saperstein; Edward A.G. Schuur; Michelle C. Mack (Forest Ecology and Management, 2023)

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget - Jennifer D. Watts; Mary Farina; John S. Kimball; Luke D. Schiferl; Zhihua Liu; Kyle A. Arndt; Donatella Zona; Ashley Ballantyne; Eugénie S. Euskirchen; Frans‐Jan W. Parmentier; Manuel Helbig; Oliver Sonnentag; et al. (Global Change Biology, 2023)
Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration ( R eco ), net ecosystem CO 2 exchange (NEE; R eco − GPP), and terrestrial methane (CH 4 ) emissions for the Arctic‐boreal zone using a satellite data‐driven process‐model for northern ecosystems (TCFM‐Arctic), calibrated and evaluated using measurements from >60 tower eddy covariance (EC) sites. We used TCFM‐Arctic to obtain daily 1‐km 2 flux estimates and annual carbon budgets for the pan‐Arctic‐boreal region. Across the domain, the model indicated an overall average NEE sink of −850 Tg CO 2 ‐C year −1 . Eurasian boreal zones, especially those in Siberia, contributed to a majority of the net sink. In contrast, the tundra biome was relatively carbon neutral (ranging from small sink to source). Regional CH 4 emissions from tundra and boreal wetlands (not accounting for aquatic CH 4 ) were estimated at 35 Tg CH 4 ‐C year −1 . Accounting for additional emissions from open water aquatic bodies and from fire, using available estimates from the literature, reduced the total regional NEE sink by 21% and shifted many far northern tundra landscapes, and some boreal forests, to a net carbon source. This assessment, based on in situ observations and models, improves our understanding of the high‐latitude carbon status and also indicates a continued need for integrated site‐to‐regional assessments to monitor the vulnerability of these ecosystems to climate change.

Response to letter to the editor on “Satellite observations document trends consistent with a boreal biome shift” - Logan T. Berner; Scott J. Goetz (Global Change Biology, 2022)

New Zealand southern right whale (Eubalaena australis; Tohorā nō Aotearoa) behavioural phenology, demographic composition, and habitat use in Port Ross, Auckland Islands over three decades: 1998–2021 - Emma L. Carroll; Leena Riekkola; Virginia Andrews-Goff; C. Scott Baker; Rochelle Constantine; Ros Cole; Kim Goetz; Robert Harcourt; David Lundquist; Catherine Meyer; Mike Ogle; Richard O’Rorke; et al. (Polar Biology, 2022)
Changes in habitat availability and prey abundance are predicted to adversely influence survival and reproduction of wildlife in the Southern Ocean. Some populations of southern right whale (SRW; Eubalaena australis ) are showing dramatic changes in habitat use. Surveys were undertaken in the austral winters of 2020 and 2021 at the key nursery and socialising ground for New Zealand SRWs: Port Ross, Auckland Islands, with 548 encounters and 599 skin biopsy samples collected. Data from these two surveys spanned peak periods of use and were used to test the hypothesis there have been shifts in the phenology, demographic composition and behaviour of SRWs using the Auckland Islands over the past three decades. The behavioural phenology and demographic composition of SRW resembles that observed in the 1990s. In contrast, the proportion of groups containing cow-calf pairs increased from 20% in the 1998 survey to 50% in 2020/21. These changes are consistent with a growing population undergoing strong recruitment, not limited by food resources. Continued use of Port Ross by all SRW demographic classes confirms this as key habitat for SRW in New Zealand waters, and we support increased enforcement of existing management measures to reduce whale-vessel interactions in this remote subantarctic archipelago.

Satellite observations document trends consistent with a boreal forest biome shift - Logan T. Berner; Scott J. Goetz (Global Change Biology, 2022)
The boreal forest biome is a major component of Earth's biosphere and climate system that is projected to shift northward due to continued climate change over the coming century. Indicators of a biome shift will likely first be evident along the climatic margins of the boreal forest and include changes in vegetation productivity, mortality, and recruitment, as well as overall vegetation greenness. However, the extent to which a biome shift is already underway remains unclear because of the local nature of most field studies, sparsity of systematic ground‐based ecological monitoring, and reliance on coarse resolution satellite observations. Here, we evaluated early indicators of a boreal forest biome shift using four decades of moderate resolution (30 m) satellite observations and biogeoclimatic spatial datasets. Specifically, we quantified interannual trends in annual maximum vegetation greenness using an ensemble of vegetation indices derived from Landsat observations at 100,000 sample sites in areas without signs of recent disturbance. We found vegetation greenness increased (greened) at 38 [29, 42] % and 22 [15, 26] % of sample sites from 1985 to 2019 and 2000 to 2019, whereas vegetation greenness decreased (browned) at 13 [9, 15] % and 15 [13, 19] % of sample sites during these respective periods [95% Monte Carlo confidence intervals]. Greening was thus 3.0 [2.6, 3.5] and 1.5 [0.8, 2.0] times more common than browning and primarily occurred in cold sparsely treed areas with high soil nitrogen and moderate summer warming. Conversely, browning primarily occurred in the climatically warmest margins of both the boreal forest biome and major forest types (e.g., evergreen conifer forests), especially in densely treed areas where summers became warmer and drier. These macroecological trends reflect underlying shifts in vegetation productivity, mortality, and recruitment that are consistent with early stages of a boreal biome shift.

Climate mediates the relationship between plant biodiversity and forest structure across the United States - Christopher R. Hakkenberg; Scott J. Goetz (Global Ecology and Biogeography, 2021)
Aim Empirical biodiversity – forest structure relationships (BSRs) underlie the use of forest structure as a remotely sensible proxy of biodiversity. However, little is known about how BSRs generalize to continental scales or how climate interacts with structure to drive local patterns in plant diversity. Resolving these research gaps in macrosystems ecology will strengthen our understanding of the biogeography of plant diversity, with implications for global‐scale biodiversity mapping. Location USA. Time period Contemporary. Major taxa studied Vascular plants and trees. Methods We combined climate variables with field measurements and airborne lidar from all forest and woodland plots in the National Ecological Observatory Network (NEON) to characterize the role of climate in constraining BSRs across the United States. Spatial generalized linear mixed models were used to quantify the individual and joint effects of structure and climate on vascular plant and tree diversity. Results These findings provide evidence for broad‐scale BSRs across the USA; namely, between plant/tree diversity and forest structural metrics in the vertical and horizontal planes. Vascular plant diversity was positively related to horizontally heterogeneous and bottom‐skewed canopies, whereas tree diversity was positively associated with canopy cover and structural heterogeneity. In addition, climate variables related to stress (negatively), energy (positively) and seasonality (negatively) affected broad‐scale patterns in diversity, with water availability (but not temperature) exerting significant effects on structural conditions. Importantly, climate and structure interact to explain variance in BSRs along coldness, mean temperature and evapotranspiration gradients. Main conclusions Our findings reinforce the importance of local context dependence in assessing non‐stationary biogeographical patterns in forest biodiversity, as well as the unique ways that forest structure and climate interact to constrain plant diversity. Beyond these theoretical insights, this study provides an empirical foundation for generalizing remotely sensed estimates of climate and forest structure to model biodiversity over vast extents.

Climate change decreases the cooling effect from postfire albedo in boreal North America - Stefano Potter; Kylen Solvik; Angela Erb; Scott J. Goetz; Jill F. Johnstone; Michelle C. Mack; James T. Randerson; Miguel O. Román; Crystal L. Schaaf; Merritt R. Turetsky; Sander Veraverbeke; Xanthe J. Walker; et al. (Global Change Biology, 2020)
Fire is a primary disturbance in boreal forests and generates both positive and negative climate forcings. The influence of fire on surface albedo is a predominantly negative forcing in boreal forests, and one of the strongest overall, due to increased snow exposure in the winter and spring months. Albedo forcings are spatially and temporally heterogeneous and depend on a variety of factors related to soils, topography, climate, land cover/vegetation type, successional dynamics, time since fire, season, and fire severity. However, how these variables interact to influence albedo is not well understood, and quantifying these relationships and predicting postfire albedo becomes increasingly important as the climate changes and management frameworks evolve to consider climate impacts. Here we developed a MODIS‐derived ‘blue sky’ albedo product and a novel machine learning modeling framework to predict fire‐driven changes in albedo under historical and future climate scenarios across boreal North America. Converted to radiative forcing (RF), we estimated that fires generate an annual mean cooling of −1.77 ± 1.35 W/m 2 from albedo under historical climate conditions (1971–2000) integrated over 70 years postfire. Increasing postfire albedo along a south–north climatic gradient was offset by a nearly opposite gradient in solar insolation, such that large‐scale spatial patterns in RF were minimal. Our models suggest that climate change will lead to decreases in mean annual postfire albedo, and hence a decreasing strength of the negative RF, a trend dominated by decreased snow cover in spring months. Considering the range of future climate scenarios and model uncertainties, we estimate that for fires burning in the current era (2016) the cooling effect from long‐term postfire albedo will be reduced by 15%–28% due to climate change.

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

Detecting early warning signals of tree mortality in boreal North America using multiscale satellite data - Brendan M. Rogers; Kylen Solvik; Edward H. Hogg; Junchang Ju; Jeffrey G. Masek; Michael Michaelian; Logan T. Berner; Scott J. Goetz (Global Change Biology, 2018)
Increasing tree mortality from global change drivers such as drought and biotic infestations is a widespread phenomenon, including in the boreal zone where climate changes and feedbacks to the Earth system are relatively large. Despite the importance for science and management communities, our ability to forecast tree mortality at landscape to continental scales is limited. However, two independent information streams have the potential to inform and improve mortality forecasts: repeat forest inventories and satellite remote sensing. Time series of tree‐level growth patterns indicate that productivity declines and related temporal dynamics often precede mortality years to decades before death. Plot‐level productivity, in turn, has been related to satellite‐based indices such as the Normalized difference vegetation index ( NDVI ). Here we link these two data sources to show that early warning signals of mortality are evident in several NDVI ‐based metrics up to 24 years before death. We focus on two repeat forest inventories and three NDVI products across western boreal North America where productivity and mortality dynamics are influenced by periodic drought. These data sources capture a range of forest conditions and spatial resolution to highlight the sensitivity and limitations of our approach. Overall, results indicate potential to use satellite NDVI for early warning signals of mortality. Relationships are broadly consistent across inventories, species, and spatial resolutions, although the utility of coarse‐scale imagery in the heterogeneous aspen parkland was limited. Longer‐term NDVI data and annually remeasured sites with high mortality levels generate the strongest signals, although we still found robust relationships at sites remeasured at a typical 5 year frequency. The approach and relationships developed here can be used as a basis for improving forest mortality models and monitoring systems.

Toxic, invasive treefrog creates evolutionary trap for native gartersnakes - Scott M. Goetz; Craig Guyer; Scott M. Boback; Christina M. Romagosa (Biological Invasions, 2018)

Vulnerability of eastern US tree species to climate change - Brendan M. Rogers; Patrick Jantz; Scott J. Goetz (Global Change Biology, 2017)
Climate change is expected to alter the distribution of tree species because of critical environmental tolerances related to growth, mortality, reproduction, disturbances, and biotic interactions. How this is realized in 21st century remains uncertain, in large part due to limitations on plant migration and the impacts of landscape fragmentation. Understanding these changes is of particular concern for forest management, which requires information at an appropriately fine spatial resolution. Here we provide a framework and application for tree species vulnerability to climate change in the eastern United States that accounts for influential drivers of future distributions. We used species distribution models to project changes in habitat suitability at 800 m for 40 tree species that vary in physiology, range, and environmental niche. We then developed layers of adaptive capacity based on migration potential, forest fragmentation, and propagule pressure. These were combined into metrics of vulnerability, including an overall index and spatially explicit categories designed to inform management. Despite overall favorable changes in suitability, the majority of species and the landscape were considered vulnerable to climate change. Vulnerability was significantly exacerbated by projections of pests and pathogens for some species. Northern and high‐elevation species tended to be the most vulnerable. There were, however, some notable areas of particular resilience, including most of West Virginia. Our approach combines some of the most important considerations for species vulnerability in a straightforward framework, and can be used as a tool for managers to prioritize species, areas, and actions.

Ecosystem responses to climate change at a Low Arctic and a High Arctic long-term research site - John E. Hobbie; Gaius R. Shaver; Edward B. Rastetter; Jessica E. Cherry; Scott J. Goetz; Kevin C. Guay; William A. Gould; George W. Kling (Ambio, 2017)

Greater shrub dominance alters breeding habitat and food resources for migratory songbirds in Alaskan arctic tundra - Natalie T. Boelman; Laura Gough; John Wingfield; Scott Goetz; Ashley Asmus; Helen E. Chmura; Jesse S. Krause; Jonathan H. Perez; Shannan K. Sweet; Kevin C. Guay (Global Change Biology, 2015)
Climate warming is affecting the Arctic in multiple ways, including via increased dominance of deciduous shrubs. Although many studies have focused on how this vegetation shift is altering nutrient cycling and energy balance, few have explicitly considered effects on tundra fauna, such as the millions of migratory songbirds that breed in northern regions every year. To understand how increasing deciduous shrub dominance may alter breeding songbird habitat, we quantified vegetation and arthropod community characteristics in both graminoid and shrub dominated tundra. We combined measurements of preferred nest site characteristics for Lapland longspurs ( Calcarius lapponicus ) and Gambel's White‐crowned sparrows ( Zonotrichia leucophrys gambelii ) with modeled predictions for the distribution of plant community types in the Alaskan arctic foothills region for the year 2050. Lapland longspur nests were found in sedge‐dominated tussock tundra where shrub height does not exceed 20 cm, whereas White‐crowned sparrows nested only under shrubs between 20 cm and 1 m in height, with no preference for shrub species. Shrub canopies had higher canopy‐dwelling arthropod availability (i.e. small flies and spiders) but lower ground‐dwelling arthropod availability (i.e. large spiders and beetles). Since flies are the birds' preferred prey, increasing shrubs may result in a net enhancement in preferred prey availability. Acknowledging the coarse resolution of existing tundra vegetation models, we predict that by 2050 there will be a northward shift in current White‐crowned sparrow habitat range and a 20–60% increase in their preferred habitat extent, while Lapland longspur habitat extent will be equivalently reduced. Our findings can be used to make first approximations of future habitat change for species with similar nesting requirements. However, we contend that as exemplified by this study's findings, existing tundra modeling tools cannot yet simulate the fine‐scale habitat characteristics that are critical to accurately predicting future habitat extent for many wildlife species.

Ten ways remote sensing can contribute to conservation - Robert A. Rose; Dirck Byler; J. Ron Eastman; Erica Fleishman; Gary Geller; Scott Goetz; Liane Guild; Healy Hamilton; Matt Hansen; Rachel Headley; Jennifer Hewson; Ned Horning; et al. (Conservation Biology, 2015)
In an effort to increase conservation effectiveness through the use of Earth observation technologies, a group of remote sensing scientists affiliated with government and academic institutions and conservation organizations identified 10 questions in conservation for which the potential to be answered would be greatly increased by use of remotely sensed data and analyses of those data. Our goals were to increase conservation practitioners’ use of remote sensing to support their work, increase collaboration between the conservation science and remote sensing communities, identify and develop new and innovative uses of remote sensing for advancing conservation science, provide guidance to space agencies on how future satellite missions can support conservation science, and generate support from the public and private sector in the use of remote sensing data to address the 10 conservation questions. We identified a broad initial list of questions on the basis of an email chain‐referral survey. We then used a workshop‐based iterative and collaborative approach to whittle the list down to these final questions (which represent 10 major themes in conservation): How can global Earth observation data be used to model species distributions and abundances? How can remote sensing improve the understanding of animal movements? How can remotely sensed ecosystem variables be used to understand, monitor, and predict ecosystem response and resilience to multiple stressors? How can remote sensing be used to monitor the effects of climate on ecosystems? How can near real‐time ecosystem monitoring catalyze threat reduction, governance and regulation compliance, and resource management decisions? How can remote sensing inform configuration of protected area networks at spatial extents relevant to populations of target species and ecosystem services? How can remote sensing‐derived products be used to value and monitor changes in ecosystem services? How can remote sensing be used to monitor and evaluate the effectiveness of conservation efforts? How does the expansion and intensification of agriculture and aquaculture alter ecosystems and the services they provide? How can remote sensing be used to determine the degree to which ecosystems are being disturbed or degraded and the effects of these changes on species and ecosystem functions?

Projected Tree Species Redistribution Under Climate Change: Implications for Ecosystem Vulnerability Across Protected Areas in the Eastern United States - Scott G. Zolkos; Patrick Jantz; Tina Cormier; Louis R. Iverson; Daniel W. McKenney; Scott J. Goetz (Ecosystems, 2015)

Vegetation productivity patterns at high northern latitudes: a multi‐sensor satellite data assessment - Kevin C. Guay; Pieter S. A. Beck; Logan T. Berner; Scott J. Goetz; Alessandro Baccini; Wolfgang Buermann (Global Change Biology, 2014)
Satellite‐derived indices of photosynthetic activity are the primary data source used to study changes in global vegetation productivity over recent decades. Creating coherent, long‐term records of vegetation activity from legacy satellite data sets requires addressing many factors that introduce uncertainties into vegetation index time series. We compared long‐term changes in vegetation productivity at high northern latitudes (>50°N), estimated as trends in growing season NDVI derived from the most widely used global NDVI data sets. The comparison included the AVHRR ‐based GIMMS ‐ NDVI version G ( GIMMS g ) series, and its recent successor version 3g ( GIMMS 3g ), as well as the shorter NDVI records generated from the more modern sensors, SeaWi FS , SPOT ‐ VGT , and MODIS . The data sets from the latter two sensors were provided in a form that reduces the effects of surface reflectance associated with solar and view angles. Our analysis revealed large geographic areas, totaling 40% of the study area, where all data sets indicated similar changes in vegetation productivity over their common temporal record, as well as areas where data sets showed conflicting patterns. The newer, GIMMS 3g data set showed statistically significant ( α = 0.05) increases in vegetation productivity (greening) in over 15% of the study area, not seen in its predecessor ( GIMMS g ), whereas the reverse was rare ( GIMMS g , particularly in Eurasia where greening is especially pronounced in the GIMMS 3g data. Our findings highlight both critical uncertainties and areas of confidence in the assessment of ecosystem‐response to climate change using satellite‐derived indices of photosynthetic activity. Broader efforts are required to evaluate NDVI time series against field measurements of vegetation growth, primary productivity, recruitment, mortality, and other biological processes in order to better understand ecosystem responses to environmental change over large areas.

Vegetation controls on northern high latitude snow‐albedo feedback: observations and CMIP 5 model simulations - Michael M. Loranty; Logan T. Berner; Scott J. Goetz; Yufang Jin; James T. Randerson (Global Change Biology, 2014)
The snow‐masking effect of vegetation exerts strong control on albedo in northern high latitude ecosystems. Large‐scale changes in the distribution and stature of vegetation in this region will thus have important feedbacks to climate. The snow‐albedo feedback is controlled largely by the contrast between snow‐covered and snow‐free albedo (Δα), which influences predictions of future warming in coupled climate models, despite being poorly constrained at seasonal and century time scales. Here, we compare satellite observations and coupled climate model representations of albedo and tree cover for the boreal and A rctic region. Our analyses reveal consistent declines in albedo with increasing tree cover, occurring south of latitudinal tree line, that are poorly represented in coupled climate models. Observed relationships between albedo and tree cover differ substantially between snow‐covered and snow‐free periods, and among plant functional type. Tree cover in models varies widely but surprisingly does not correlate well with model albedo. Furthermore, our results demonstrate a relationship between tree cover and snow‐albedo feedback that may be used to accurately constrain high latitude albedo feedbacks in coupled climate models under current and future vegetation distributions.

Plant response to climate change along the forest‐tundra ecotone in northeastern Siberia - Logan T. Berner; Pieter S. A. Beck; Andrew G. Bunn; Scott J. Goetz (Global Change Biology, 2013)
Russia's boreal (taiga) biome will likely contract sharply and shift northward in response to 21st century climatic change, yet few studies have examined plant response to climatic variability along the northern margin. We quantified climate dynamics, trends in plant growth, and growth–climate relationships across the tundra shrublands and Cajander larch ( Larix cajanderi Mayr.) woodlands of the Kolyma river basin (657 000 km 2 ) in northeastern Siberia using satellite‐derived normalized difference vegetation indices ( NDVI ), tree ring‐width measurements, and climate data. Mean summer temperatures ( T s ) increased 1.0 °C from 1938 to 2009, though there was no trend ( P > 0.05) in growing year precipitation or climate moisture index ( CMI gy ). Mean summer NDVI ( NDVI s ) increased significantly from 1982 to 2010 across 20% of the watershed, primarily in cold, shrub‐dominated areas. NDVI s positively correlated ( P T s across 56% of the watershed ( r = 0.52 ± 0.09, mean ± SD), principally in cold areas, and with CMI gy across 9% of the watershed ( r = 0.45 ± 0.06), largely in warm areas. Larch ring‐width measurements from nine sites revealed that year‐to‐year (i.e., high‐frequency) variation in growth positively correlated ( P r = 0.40) and prior summer CMI ( r = 0.40) from 1938 to 2007. An unexplained multi‐decadal (i.e., low‐frequency) decline in annual basal area increment ( BAI ) occurred following the mid‐20th century, but over the NDVI record there was no trend in mean BAI ( P > 0.05), which significantly correlated with NDVI s ( r = 0.44, P

Carbon Accumulation Patterns During Post-Fire Succession in Cajander Larch (Larix cajanderi) Forests of Siberia - Heather D. Alexander; Michelle C. Mack; Scott Goetz; Michael M. Loranty; Pieter S. A. Beck; Kamala Earl; Sergey Zimov; Sergey Davydov; Catharine C. Thompson (Ecosystems, 2012)

The impacts and implications of an intensifying fire regime on Alaskan boreal forest composition and albedo - PIETER S. A. BECK; SCOTT J. GOETZ; MICHELLE C. MACK; HEATHER D. ALEXANDER; YUFANG JIN; JAMES T. RANDERSON; M. M. LORANTY (Global Change Biology, 2011)
Climate warming and drying are modifying the fire dynamics of many boreal forests, moving them towards a regime with a higher frequency of extreme fire years characterized by large burns of high severity. Plot‐scale studies indicate that increased burn severity favors the recruitment of deciduous trees in the initial years following fire. Consequently, a set of biophysical effects of burn severity on postfire boreal successional trajectories at decadal timescales have been hypothesized. Prominent among these are a greater cover of deciduous tree species in intermediately aged stands after more severe burning, with associated implications for carbon and energy balances. Here we investigate whether the current vegetation composition of interior Alaska supports this hypothesis. A chronosequence of six decades of vegetation regrowth following fire was created using a database of burn scars, an existing forest biomass map, and maps of albedo and the deciduous fraction of vegetation that we derived from Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery. The deciduous fraction map depicted the proportion of aboveground biomass in deciduous vegetation, derived using a RandomForest algorithm trained with field data sets ( n =69, 71% variance explained). Analysis of the difference Normalized Burn Ratio, a remotely sensed index commonly used as an indicator of burn severity, indicated that burn size and ignition date can provide a proxy of burn severity for historical fires. LIDAR remote sensing and a bioclimatic model of evergreen forest distribution were used to further refine the stratification of the current landscape by burn severity. Our results show that since the 1950s, more severely burned areas in interior Alaska have produced a vegetation cohort that is characterized by greater deciduous biomass. We discuss the importance of this shift in vegetation composition due to climate‐induced changes in fire severity for carbon sequestration in forest biomass and surface reflectance (albedo), among other feedbacks to climate.

Scaling an Instantaneous Model of Tundra NEE to the Arctic Landscape - Michael M. Loranty; Scott J. Goetz; Edward B. Rastetter; Adrian V. Rocha; Gaius R. Shaver; Elyn R. Humphreys; Peter M. Lafleur (Ecosystems, 2011)

Lidar remote sensing variables predict breeding habitat of a Neotropical migrant bird - Scott J. Goetz; Daniel Steinberg; Matthew G. Betts; Richard T. Holmes; Patrick J. Doran; Ralph Dubayah; Michelle Hofton (Ecology, 2010)
A topic of recurring interest in ecological research is the degree to which vegetation structure influences the distribution and abundance of species. Here we test the applicability of remote sensing, particularly novel use of waveform lidar measurements, for quantifying the habitat heterogeneity of a contiguous northern hardwoods forest in the northeastern United States. We apply these results to predict the breeding habitat quality, an indicator of reproductive output of a well‐studied Neotropical migrant songbird, the Black‐throated Blue Warbler ( Dendroica caerulescens ). We found that using canopy vertical structure metrics provided unique information for models of habitat quality and spatial patterns of prevalence. An ensemble decision tree modeling approach (random forests) consistently identified lidar metrics describing the vertical distribution and complexity of canopy elements as important predictors of habitat use over multiple years. Although other aspects of habitat were important, including the seasonality of vegetation cover, the canopy structure variables provided unique and complementary information that systematically improved model predictions. We conclude that canopy structure metrics derived from waveform lidar, which will be available on future satellite missions, can advance multiple aspects of biodiversity research, and additional studies should be extended to other organisms and regions.

Urbanization and the Loss of Resource Lands in the Chesapeake Bay Watershed - Patrick Jantz; Scott Goetz; Claire Jantz (Environmental Management, 2005)

Assessing Development Pressure in the Chesapeake Bay Watershed: An Evaluation of Two Land-Use Change Models - Peter R. Claggett; Claire A. Jantz; Scott J. Goetz; Carin Bisland (Environmental Monitoring and Assessment, 2004)

Remotely Sensed Interannual Variations and Trends in Terrestrial Net Primary Productivity 1981?2000 - Mingkui Cao; Stephen D. Prince; Jennifer Small; Scott J. Goetz (Ecosystems, 2004)

Molecular analysis of two cytochrome P450 monooxygenase genes required for paxilline biosynthesis in Penicillium paxilli, and effects of paxilline intermediates on mammalian maxi-K ion channels - L. K. McMillan; R. L. Carr; C. A. Young; J. W. Astin; R. G. T. Lowe; E. J. Parker; G. B. Jameson; S. C. Finch; C. O. Miles; O. B. McManus; W. A. Schmalhofer; M. L. Garcia; et al. (Molecular Genetics and Genomics, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)